2009
DOI: 10.5194/acp-9-9143-2009
|View full text |Cite
|
Sign up to set email alerts
|

Increase of upper troposphere/lower stratosphere wave baroclinicity during the second half of the 20th century

Abstract: Abstract.A strengthening of the equatorward temperature gradient in the upper troposphere/lower stratosphere (UTLS), at subtropics and midlatitudes, is consistently reproduced in several modelling studies of the atmospheric response to the increase of greenhouse gas radiative forcing. Some of those studies suggest an increase of the baroclinicity in the UTLS region because of the enhanced meridional temperature gradient.This study presents observational evidence of an increase of the baroclinic wave components… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…A possible explanation is that folds in these regions develop in conjunction with PV streamers characteristic of Rossby wave breaking. This hypothesis is supported by Wernli and Sprenger [2007], who found maxima of PV streamer frequencies at 350 K over the eastern North Pacific and the North Atlantic in DJF (most shallow folds are centered around this isentrope; see section 4.2 and Figure 6), and Castanheira et al [2009], who reported on a link between baroclinic wave activity and double tropopause frequency. The high fold frequency and the distinct double-peak structure over the Mediterranean and Middle East in JJA are results of a complex interplay between the STJ and the Asian monsoon anticyclone [Traub and Lelieveld, 2003].…”
Section: Geographical Distributionmentioning
confidence: 99%
“…A possible explanation is that folds in these regions develop in conjunction with PV streamers characteristic of Rossby wave breaking. This hypothesis is supported by Wernli and Sprenger [2007], who found maxima of PV streamer frequencies at 350 K over the eastern North Pacific and the North Atlantic in DJF (most shallow folds are centered around this isentrope; see section 4.2 and Figure 6), and Castanheira et al [2009], who reported on a link between baroclinic wave activity and double tropopause frequency. The high fold frequency and the distinct double-peak structure over the Mediterranean and Middle East in JJA are results of a complex interplay between the STJ and the Asian monsoon anticyclone [Traub and Lelieveld, 2003].…”
Section: Geographical Distributionmentioning
confidence: 99%
“…[3] Randel et al [2007] and Pan et al [2009] suggested that the mechanisms responsible for the formation of double tropopause structures may include contributions from a thermally direct secondary circulation around the subtropical jet, which is associated with developing baroclinic waves and is accompanied by an excursion of the tropical tropopause over the extratropical one. Castanheira et al [2009] suggested that DT events must be associated with baroclinic waves in the subtropical upper troposphere/lower stratosphere (UTLS). Such an association would explain the significant positive trends in the frequency of DT events identified in radiosonde data, concurrent with significant positive trends in the energy of baroclinic waves as seen in reanalysis data.…”
Section: Introductionmentioning
confidence: 99%
“…Sausen and Santer [2003], Santer et al [2003a], and Añel et al [2006] have suggested that changes in the altitude of the tropopause caused by cooling in the stratosphere and warming in the troposphere [Santer et al, 2003b] may be a sensitive indicator of anthropogenic climate change. Recently, Castanheira et al [2009] presented observational evidence of increases in wave baroclinicity in the upper troposphere and lower stratosphere (UTLS) at midlatitudes due to increase in greenhouse gas radiative forcing. They also interpreted significant positive trends in the frequency of double tropopause events in the radiosonde data as a manifestation of an increase in UTLS baroclinicity.…”
Section: Introductionmentioning
confidence: 99%